Exploring Arab folk literature - Cachia, Pierre 1921-2017 (Edinburgh Univ. Press, 2011)
The character and range of Arab folk literature are investigated by Pierre Cachia in this collection of his essays in the field he has pioneered. These are arranged into three sections. The first traces the changing relationship between Arab folk and elite literatures, the gradual elaboration of certain genres, and the career of a folk poet. The author then devotes a substantial section to the consideration of single or related texts. Finally he comments on social and cultural implications and on differences of attitudes of folk and elite towards sensitive issues. This book represents an insightful contribution to our understanding of Arab folk literature and will be of relevance to anyone with an interest in Arab literary creativity. Key Features Collects in one volume Pierre Cachia's observations on material acquired after his seminal "Popular Narrative Ballads of Modern Egypt" (1989). Includes two previously unpublished essays. Examines the history, texts, and social and cultural implications of the tradition. Presents a revised and updated transcription system based on pronunciation of the language - far more suited to oral forms of literature. - Pierre Cachia is Professor Emeritus, Arabic Language and Literature, Columbia University. He is the joint editor of Islam: Past Influence and Present Challenge, the festschrift published by EUP for William Montgomery Watt (1984). He also jointly authored with William Montgomery Watt A History of Islamic Spain (1996). (Klappentext)
Keywords: Folk literature, Arabic / History and criticism; Arabisch; Volksliteratur